The Contribution of Online and Offline Travel Agent Reservations to Increase Room Occupancy at The Westin Resort Nusa Dua, Bali - Ni Luh Ayu Feby Handayani; I Ketut Sutama; Ni Putu Wiwiek Ary Susyarini; Putu Yunita Wacana Sari; I Made Sudiarta (International Journal of Travel, Hospitality and Events, 2023)
Purpose: This research focuses on the contribution of room reservations and occupancy. The problem under investigation is to compare the contributions of online and offline travel agents to room occupancy. This study aimed to determine the magnitude and comparison of the gift of online and offline travel agents to room occupancy at The Westin Resort Nusa Dua, Bali. Research methods: Data were collected using observation, documentation, and a literature study with a quantitative and qualitative descriptive approach. Results and discussion: The results of this study indicate that in 2018 online travel agents contributed 36,88% and offline travel agents contributed 23.74% of the total room occupancy for a year, 78.95%; in 2019, online travel agents contributed 38.55%, and offline travel agents contributed 24.69% of the total room occupancy for a year 84.39%, and in 2020 online travel agents contributed 34.04% and offline travel agents contributed 23.34% of the total room occupancy for a year 19.25%. Implication: Based on that, it shows that reservations through online travel agents have a more significant contribution than offline travel agents. Online and offline Travel Agents with the most dominant assistance were Citrip, with a 9% donation, and Kliknbook and Mandira, contributing 3%. During the COVID-19 pandemic, the gift of online and offline travel agents decreased significantly due to many cancellations.   Keywords: reservation, online travel agent, offline travel agent, room occupancy.